(untitled) (Journal of Engineering, 2011)
Eight reinforced concrete beams were tested in order to investigate the effective embedded length of the longitudinal reinforcement bar in self compacted concrete (SCC). All specimens were reinforced with a uni-reinforced bar, six of them embedded in self compacted concrete and the others embedded in normal concrete. The test was carried out on simply supported beams loaded at two points. At the end of the reinforcement bar slip was measured, also under the loading point slip and the bar strain were measured. The investigated variables in this study were: The bar diameter, and the available embedded length. To find out how these variables influence the embedded length in case of using self compacted concrete and comparing it with the normal concrete. The results show that, with increasing the bar diameter, bond stress slightly decreases, while with increasing the embedded length of the longitudinal bar the bond stress decreases and this improves the mode of the bond failure, especially for the specimens having small bar diameter.